Nanopolycrystalline materials; a general atomistic model for simulation - Sayle, Dean C.; Mangili, Benoit C.; Price, David W.; Sayle, Thi X. T. (Royal Society of Chemistry, 2010)
We present a general strategy for generating full atomistic models of nanopolycrystalline materials including bulk and thin film. In particular, models for oxidenanoparticles were constructed using simulated amorphisation and crystallisation and used to populate a library of oxidenanoparticles (amorphous and crystalline) with different radii. Nanoparticles were then taken from this library and positioned, within a specific volume, using Monte Carlo techniques, to facilitate a tight-packed structure. The grain-size distribution of the polycrystalline material was controlled by selecting particular sized nanoparticles from the library. The (randomly oriented) grains facilitated a polycrystalline oxide, which comprised a network of general grain-boundaries. To help validate the model, gas diffusion through the (polycrystalline) oxide material was then simulated and the activation energy calculated directly. Specifically, we explored Hetransport in UO2, which is an important material with respect to both civilian and military applications. We found that Hetransport proceeds much faster through the grain-boundary and grain-junction network compared with intracrystalline UO2 regions, in accordance with experiment.